Visible-Light-Mediated Regioselective Chlorosulfonylation of Acrylamides - Zurro, Mercedes; Torres-Oya, Sergio; Otárola, Guillermo G.; Vaquero, Juan José; Merino, Estíbaliz (Synthesis, 2023)
A one-step chlorosulfonylation of acrylamides via a photocatalytic redox process is described. This reaction provides α-chlorosulfonylamides with a quaternary center with high regioselectivity via radical process. It is amenable to a broad range of substrates and the products are obtained in moderate to good yields.
Keywords: acrylamides; difunctionalization of alkenes; photocatalysis; chlorosulfonylation; α-chlorosulfones